Behavior notes and prey spectrum of three species of the bee-hunting wasp Trachypus Klug (Hymenoptera: Apoidea) - Pereira, Felipe Walter; Gonçalves, Rodrigo Barbosa (Papéis Avulsos de Zoologia, 2021)
Trachypus Klug is a Neotropical genus of crabronid wasps comprising 31 ground-nesting species. Its species can be solitary or communal, and two diet ranges are known: they can forage on several bee subfamilies and wasps; or can be specialists on stingless bees. Natural history observations are scarce nowadays but are essential to contextualize ecological and evolutionary studies. Here we report new records and give biological notes for Trachypus elongatus (Fabricius, 1804), Trachypus taschenbergi Rubio-Espina, 1975, and Trachypus varius (Taschenberg, 1875). Observations and samplings were carried out twice a month, during one year in the city of Curitiba, southern Brazil. Besides field observations, circular statistics were used to analyze seasonality. All species nest in sloped soil and are solitary. Trachypus elongatus and T. taschenbergi were active during most of the year with marked seasonality in the late spring and early summer. Both species were observed hunting only stingless bees, with T. elongatus specialized on Trigona spinipes (Fabricius, 1793), and T. taschenbergi specialized on Paratrigona subnuda Moure, 1947 drones. Trachypus varius was observed only in January and one female was recorded foraging on a Paratrigona subnuda worker. Our observations provide additional data for understanding the biology of bee-hunting wasps, and this is the first study to bring information for T. taschenbergi and T. varius. Our data corroborate that some species of the genus Trachypus are specialized on stingless bees.